Bagaimana Jika Ki Hajar Dewantara Mengajar Pendidikan Jasmani? - Rachman, Hari Amirullah (Jurnal Pendidikan Jasmani Indonesia, 2015)
In the learning process of the physical education at the elementary school, actually there are many thoughts of Ki Hajar Dewantara, the national education's father, still relevant to and necessary to contemplate to be applied by the physical education teachers. His thoughts, such as independence principality as the educational principality, are characterizing the self-supporting, productive and creative, and also high-disciplined human being. Implicitly the thoughts are in accordance with the target of the physical education that is to develop discipline, skill, fitness, reasoning, and social emotion. If Ki Hajar Dewantara becomes a physical education teacher, there will be no doubt that his thoughts will be used as main foundations for efficiently and effectively physical education learning process, to reach the targets of national education. Keyword: Ki Hajar Dewantara, Physical Education, Elementary School teacher.